PENGARUH SHOPPING EXPERIENCE TERHADAP BRAND IMAGE KAWASAN OBJEK WISATA BELANJA BATIK TRUSMI (Survei terhadap Pengunjung Kawasan Objek Wisata Belanja Batik Trusmi Kabupaten Cirebon) - Novianti, Ranny Achni; Purnama, Ridwan (THE Journal : Tourism and Hospitality Essentials Journal, 2011)
Kabupaten Cirebon is one of regencies in West java has tourism potential can be relied, and the one of destination is Kawasan Objek Wisata Belanja Batik Trusmi. Kawasan Objek Wisata Belanja Batik Trusmi is a shopping tourism area that offers a variety oftypicalCirebonanbatikcollection. The number of tourist visits on Kawasan Objek Wisata Belanja Batik Trusmi has decreased from 2007 to 2010. The most drastic decrease of tourist visit happened in 2010. Shopping experience is one of marketing strategy that can be used to increase the number of visit. In connection with these to research studies conducted on the influence shopping experience toward brand image Kawasan Objek Wisata Belanja Batik Trusmi. The purpose of this research is to find shopping experience influence brand image to Kawasan Objek Wisata belanja Batik Trusmi. Promotion mix consists of price, characteristics ofdestinations, merchandising, authenticity, and staff service quality. Technique of sampling is simple random sampling.The method in that used in this research is explanatory survey by using ordinal scale.Analyze from this research use Path Analysis with a computer software tools SPSS 19.0. The result of this research is shopping experience influence significantly 71,48% and the rest influence other factors. Based on the result of statistical test results were obtained, there were three variables of shopping experience which had an influence on brand image of price, merchandising, and authenticity and there was two variables that had no effect on brand image was characteristics ofdestinations and staff service quality.That it can be concluded that price, merchandising, and authenticity strong influence brand image on Kawasan Objek Wisata Belanja Batik Trusmi.